1996
DOI: 10.1093/bja/76.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive failures after general anaesthesia for day-case surgery

Abstract: Patients are normally thought to have recovered from general anaesthesia within a few hours after day-case surgery. Previous recovery studies using objective psychometric tests showed a return to baseline values within this period. Nevertheless, patients are advised about what activities they should not undertake in the subsequent 24 h because it is feared that the residual anaesthetic effects may impair their ability. These studies did not follow patients out of hospital and their relevance to the real world … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 11 publications
3
20
0
3
Order By: Relevance
“…Alterations in cognitive function following general anaesthesia place patients at higher risks from postoperative adverse events. In one study, patients undergoing ambulatory anaesthesia reported significantly more cognitive failures, including failures of perception, memory or misdirected action, 3 days postoperatively, compared to patients undergoing procedures under local anaesthesia [15].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in cognitive function following general anaesthesia place patients at higher risks from postoperative adverse events. In one study, patients undergoing ambulatory anaesthesia reported significantly more cognitive failures, including failures of perception, memory or misdirected action, 3 days postoperatively, compared to patients undergoing procedures under local anaesthesia [15].…”
Section: Discussionmentioning
confidence: 99%
“…The extent of patient recovery from the residual effects of anesthetics may be determined by clinical, psychomotor and cognitive tests (10). Cognitive function impairment occurs often and consistently, particularly in the elderly (11). …”
Section: Introductionmentioning
confidence: 99%
“…Tzabar and colleagues reported a greater number of cognitive lapses in younger patients when the patients used a cognitive failures questionnaire, which allows self-assessment. They did not use objective testing [5].…”
Section: Introductionmentioning
confidence: 99%